AB0400 Efficacy and safety of intravenous and subcutaneous tocilizumab in a cohort of patients affected by rheumatoid arthritis in real-life. (15th June 2017) - Pomponio, G; Tontini, C; Angeletti, A; Olivari, D; Benfaremo, D; Manfredi, L; Danieli, MG; Fraticelli, P; Luchetti, MM; Moroncini, G; Gabrielli, A
Abstract : Background: Tocilizumab (TCZ) is a humanized monoclonal anti-interleukin-6 receptor antibody, used for the treatment of moderate to severe rheumatoid arthritis (RA). Although TCZ has been proved to be highly effective and safe in RA patients in large clinical trials, few data are available from real-life practice [1]. Objectives: To evaluate efficacy, safety and retention rate of intravenous (IV) and subcutaneous (SC) TCZ in a real-world setting. Methods: We evaluated patients affected by moderate-to-severe RA and treated with TCZ from April 2010 to January 2017. Data of patients treated with IV-TCZ until January 2017 were collected retrospectively, while patients treated with either IV or SC-TCZ from January 2015 were included in a prospective cohort and assessed for disease activity, treatment discontinuation and/or onset of adverse events (AEs). DAS28-CRP, CDAI and SDAI scores were used for disease activity assessment and paired t test was used for statistical analysis. Treatment retention rate was estimated by Kaplan-Meier method. Results: We evaluated 100 patients, 58 treated with IV-TCZ (8 mg/kg every 4w), 16 with SC-TCZ (162 mg every week), 26 switched from IV to SC during followup and 6 of these returned to IV-TCZ for cutaneous intolerance (80 females, median age 63 y, median duration of disease 11 y, median follow-up 16 months). Seventy-eight patients (78%) were treated with monotherapy and twenty-two (22%) in combination with methotrexate. At baseline, disease activity was severe in 87% of patients, moderate in 6% and mild or inactive in 7%; at the latest follow-up 60% of patients are in clinical remission. The mean DAS28-CRP in IV-TCZ and SW-TCZ groups considered as a whole was 4.34 at baseline and 2.71 at the latest follow-up available (p<0.0001). In the SC-TCZ group, mean basal DAS28-CRP was 3.70 vs 1.89 measured at the latest follow-up (p<0.0001). Fifty-three patients (53%) discontinued TCZ because of inefficacy (19), AEs (13) or other reasons (21, mostly lost to follow-up). Infections were the most frequent AE (45.1/100 person-years), 3 cases of severe pneumonia, one required treatment discontinuation. Infusion reactions were reported in 6/58 IV-TCZ patients, while injection site reactions in 14/42 SC-TCZ patients. Six of these intolerant patients were subsequently treated with i.v. tocilizumab without reactions. We observed an overall high retention rate of IV-TCZ and SW-TCZ (91.1%, 81.2%, 70.6%, 61.3%, 57.1% and 50% at 1, 2, 3, 4, 5, and 6 years respectively). The retention rate of SC-TCZ patients at 3 years was about 77%. The difference between IV/SW-TCZ and SC-TCZ groups was not significant (Fig. 2). Conclusions: TCZ is effective, well tolerated and safe in a population of RA patients followed in a real-life setting. No unexpected AE was observed in this large population followed for a long period. Interestingly retention rate was not affected by the administration route and in real life many patients can safely shift across different administration modalities. References: Gabay C, Riek M, Hetland ML, Hauge EM, Pavelka K, Tomšič M, et al. Effectiveness of tocilizumab with and without synthetic disease-modifying antirheumatic drugs in rheumatoid arthritis: results from a European collaborative study. Ann Rheum Dis. 2015 Sep 15. Disclosure of Interest: None declared